If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(2y + -3) = 2y + -12 Reorder the terms: 4(-3 + 2y) = 2y + -12 (-3 * 4 + 2y * 4) = 2y + -12 (-12 + 8y) = 2y + -12 Reorder the terms: -12 + 8y = -12 + 2y Add '12' to each side of the equation. -12 + 12 + 8y = -12 + 12 + 2y Combine like terms: -12 + 12 = 0 0 + 8y = -12 + 12 + 2y 8y = -12 + 12 + 2y Combine like terms: -12 + 12 = 0 8y = 0 + 2y 8y = 2y Solving 8y = 2y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-2y' to each side of the equation. 8y + -2y = 2y + -2y Combine like terms: 8y + -2y = 6y 6y = 2y + -2y Combine like terms: 2y + -2y = 0 6y = 0 Divide each side by '6'. y = 0 Simplifying y = 0
| 8w+3x-2y=180 | | 12a+19b+2c+5c-6b-2a= | | x-(-9)=2 | | -8+2(4-6c)= | | 10-3x=-2(x+14) | | 2.5x-1.25=3x-2 | | b-7+5b=24 | | 37+4y-14=16y-12-5y | | 8=4m+12 | | 2(x-4)=9-2(x+1) | | 4y-2(y-1)+3= | | 2x+9=3+4x-6 | | 8x^2+4y+9=29 | | 5(4+5r)=-180 | | -3-2x=9 | | -4(v-3)=9v+38 | | 1/2y=24 | | (3-2y)(3-2y)-4y-4y=-33 | | -288=4(-8x-8) | | 5/x+2+3/4x-1=5 | | 20a+15b+4c+3c-5b-4a= | | 1.48g-11=0.10 | | 8x-7x-5=6 | | 2x^2-22x+16=0 | | 22-16=2(x-8) | | 2r-6=9-3r | | f(x)=x^3+4x^2+4x | | 3.5/4.9=7/9 | | m^3-5m-2=0 | | 35+4y-1=14y-14-2y | | k=3.5/4.9 | | 2ln(x)=ln(2)+ln(3x+-4) |